Diagnostic and prognostic utility of troponin estimation in patients presenting with syncope: a prospective cohort study. Issue 4 (12th April 2010) - Reed, Matthew J; Newby, David E; Coull, Andrew J; Prescott, Robin J; Gray, Alasdair J
Abstract : Aims: To primarily assess the value of troponin I to identify acute myocardial infarction (AMI), and second, to predict 1-month serious outcome or all-cause death in patients presenting with syncope to the Emergency Department (ED). Design: Prospective cohort study of all adult patients presenting to the ED after an episode of syncope. Methods: In admitted patients, plasma troponin I was measured 12 h after syncope, and in discharged patients, between 12 h and 7 days following discharge. Primary endpoints were the diagnosis of AMI, and the composite endpoint of serious outcome or all-cause death at 1 month. Results: Over an 8-month period, 289 patients were recruited. Troponin I was obtained in 186 admitted patients and was elevated in 13 (7%), and obtained in 103 discharged patients and was raised in only one (1%). Four patients had an AMI (1.4%) and all had ischaemic electrocardiographic (ECG) changes on their presenting ED ECG (ST segment deviation or pathological Q waves) that were 100% sensitive and 72% specific for AMI with a 100% negative predictive value. Seven of the 14 patients (50%) with a raised troponin I had a serious outcome that did not include AMI, or all-cause death compared with 16 of the 267 patients (6%) without a raised troponin (p<0.0001). Conclusions: AMI is infrequent (1.4%), and estimation of troponin I provides little additional benefit to the presenting ED ECG in identifying patients with syncope due to AMI. Troponin I should not be used to rule out AMI in adult patients presenting with isolated syncope. Troponin I may predict 1-month serious outcome or all-cause death in syncope.